Temperature stability in the sub-milliHertz band with LISA Pathfinder. Issue 3 (12th April 2019) - Armano, M; Audley, H; Baird, J; Binetruy, P; Born, M; Bortoluzzi, D; Castelli, E; Cavalleri, A; Cesarini, A; Cruise, A M; Danzmann, K; Silva, M de Deus; et al.
Abstract: LISA Pathfinder (LPF) was a technology pioneering mission designed to test key technologies required for gravitational wave detection in space. In the low frequency regime (milliHertz and below), where space-based gravitational wave observatories will operate, temperature fluctuations play a crucial role since they can couple into the interferometric measurement and the test masses' free-fall accuracy in many ways. A dedicated temperature measurement subsystem, with noise levels in 10 μ K Hz −1/2 down to 1 mHz was part of the diagnostics unit onboard LPF. In this paper we report on the temperature measurements throughout mission operations, characterize the thermal environment, estimate transfer functions between different locations, and report temperature stability (and its time evolution) at frequencies as low as 10 μ Hz, where typically values around 1 K Hz −1/2 were measured.